2011
DOI: 10.1111/j.1746-1049.2010.00121.x
|View full text |Cite
|
Sign up to set email alerts
|

Imported Skill-Biased Technological Change in Developing Countries

Abstract: This paper discusses the occurrence of skill-enhancing technology import, namely, the relationship between imports of embodied technology and widening skill-based employment differentials in low-and middle-income countries. Generalized method of moments (GMM) techniques are applied to an original panel dataset comprising 28 manufacturing sectors for 23 countries over a decade. Econometric results provide robust evidence of the determinants of widening employment differentials in low-and middle-income countries… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
61
0
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(66 citation statements)
references
References 71 publications
2
61
0
3
Order By: Relevance
“…Imports of capital equipment are considered by some authors, (Conte and Vivarelli, 2007), as a factor underling the rise of the number of educated workers and the decrease of that of the unskilled ones in the developing countries. In Tunisia, for example, they knew remarkable fluctuations during the 2000-2007 period with a steady growth since 2008 ( Figure 3).…”
Section: A Review Of the Tunisian National Potential In Ictmentioning
confidence: 99%
“…Imports of capital equipment are considered by some authors, (Conte and Vivarelli, 2007), as a factor underling the rise of the number of educated workers and the decrease of that of the unskilled ones in the developing countries. In Tunisia, for example, they knew remarkable fluctuations during the 2000-2007 period with a steady growth since 2008 ( Figure 3).…”
Section: A Review Of the Tunisian National Potential In Ictmentioning
confidence: 99%
“…For example, adopting a cross-country perspective, Meschi and Vivarelli (2009) found that trade flows with more technologically advanced countries worsen income distribution by increasing wage differentials between skilled and unskilled workers. By the same token, Conte and Vivarelli (2011) report evidence of a positive relationship between the imports of industrial machinery, equipment, and ICT capital goods and the demand for skilled labor in low and middleincome countries. Almeida (2009) reaches similar conclusions when studying eight East-Asian middleincome countries, but does not find evidence supporting SBTC in low income countries.…”
Section: Trade and Technological Change In Developing Countriesmentioning
confidence: 99%
“…If we consider two types of labor inputs, namely skilled (white-collars WC) and unskilled (blue-collars BC) and adopt a dynamic specification in order to account for adjustment costs that determine serial correlation in the employment series (see Van Reenen, 1997;Lachenmaier and Rottman, 2011;and Conte and Vivarelli, 2011), our estimating equations of the quantity effect are the following:…”
Section: The Empirical Model: Specification and Econometric Issuesmentioning
confidence: 99%
“…Major portion of the literature identified that higher trade openness increases inequality in the country for example but not limited to (Revenga, 1997;Milner and Wright, 1998;Levinsohn, 1999;Ravallion, 2001;Epifani, 2003;Lundberg and Squire, 2003;Melitz, 2003;Xu, 2003;Khondker and Raihan, 2004;Annabi et al, 2005;Milanovic, 2005;Yeaple, 2005;Bustos, 2007;Conte and Vivarelli, 2007;Meschi and Vivarelli, 2009;Barua and Chakraborty, 2010;Bergh and Nilsson, 2010;Li and Coxhead, 2011;Ezcurra and Rodriguezpose, 2013;Furusawa and Konishi, 2013;Grossman and Helpman, 2014).On the other hand, some studies concluded that trade reduces income inequality (Bourguignon and Morrisson, 1990;Wood, 1995;Calderón and Chong, 2001;Cornia and Kiiski, 2001;Ravallion, 2001;Lundberg and Squire, 2003;Wade, 2004;Milanovic and Squire, 2005;Easterly, 2006;Demir et al, 2012) and some studies found mixed results (Meschi and Vivarelli, 2009;Nissanke and Thorbecke, 2010;Castilho et al, 2012;Perera et al, 2014;Hepenstrick and Tarasov, 2015).…”
Section: Review Of Literaturementioning
confidence: 99%